‘Changing the Focus’: Co-Design of a Novel Approach for Engaging People with Dementia in Physical Activity - Claudia Meyer; Den-Ching A. Lee; Michele Callisaya; Morag E. Taylor; Katherine Lawler; Pazit Levinger; Susan Hunter; Dawn C. Mackey; Elissa Burton; Natasha Brusco; Terry Haines; Christina L. Ekegren; et al. (Nursing Reports)
Background: Promoting physical activity among people living with dementia is critical to maximise physical, cognitive and social benefits; yet the lack of knowledge, skills and confidence among health professionals, informal care partners and people with dementia deters participation. As the initial phase of a larger feasibility study, co-design was employed to develop a new model of community care, ‘Changing the Focus’, to facilitate the physical activity participation of older people living with mild dementia. Methods: Co-design methodology was utilised with nine stakeholders (with experience in referring to or providing physical activity programs and/or contributing to policy and program planning) over three workshops plus individual interviews with four care partners of people with dementia. Insights were gathered on the physical activity for people with mild dementia, referral pathways were explored and ‘personas’ were developed and refined. Materials and resources to support exercise providers and referrers to work effectively with people with mild dementia were finalised. Results: Three ‘personas’ emerged from the co-design sessions, aligned with stages of behaviour change: (1) hesitant to engage; (2) preparing to engage; and (3) actively engaged. Referral pathway discussions identified challenges related to limited resources, limited knowledge, access constraints and individual factors. Opportunities were classified as using champions, streamlining processes, recognising triggers for disengagement, influencing beliefs and attitudes, and means of communication. Conclusion: This study captured the views of physical activity referrers and providers and informal care partners in an inclusive and iterative manner. The use of co-design ensured a robust approach to facilitating participation in formal and informal physical activity options for people living with mild dementia. This study has provided the necessary framework from which to develop and test training and resources for the next stage of intervention (a feasibility trial) to improve physical activity participation for people with dementia.